Research on microbial communities in tumor microenvironments: cutting-edge dynamics and future trends from a bibliometric perspective - Tang, Xuan; Man, Changfeng; Liu, Ziyan; Gong, Dandan; Fan, Yu (Frontiers in Immunology, 2026)
BackgroundIn recent years, researchers have identified numerous potential biomarkers and therapeutic targets applicable to cancer immunotherapy, among which the role of tumor-internal microorganisms in the tumor microenvironment has been explored. However, this field is still in its early stages of development, facing limitations such as the unclear mechanisms of interaction between tumor-internal microorganisms and host immunity, as well as significant variations in microbial profiles among different tumor types and patients.ObjectiveThis study aims to explore the research hotspots and development trends of tumor-internal microorganisms through bibliometric methods and to construct a systematic knowledge map.MethodsThis study retrieved publications related to tumor-internal microorganisms from the Web of Science Core Collection (WOSCC) prior to December 22, 2025. Subsequently, the selected literature was analyzed using VOSviewer (v.1.6.20), CiteSpace (v.6.4.1R), and SCImago Graphica. In addition, we integrated PubMed data to assess status and trends in preclinical and clinical studies of intratumoral microbiota interventions for anti-tumor therapy efficacy.ResultsFrom the Web of Science database, we retrieved 1,278 relevant articles. Since 2012, the number of papers published on the intratumoral microbiota has shown an overall upward trend. China and the United States are the two major countries in this field. Keyword analysis shows that “tumor microbiome,” “gut microbiome,” “cancer,” and “Fusobacterium nucleatum” are frequent terms. 11 keyword groups have been identified, among which “tumor immunotherapy” and “immune microenvironment” form two important groups. A total of 69 preclinical and clinical studies has intervened in intratumoral microbiota and affected anti-tumor treatment outcomes. Among them, 25 studies involving Fusobacterium nucleatum account for a large proportion. However, most of these studies are still at the basic or preclinical stage, and clinical translation evidence is limited.